The Human Nature of a University - Goheen, Robert F. (Robert Francis), 1919-2008 (Book collections on Project MUSE., 1969)
This is a collection of excerpts from the public addresses of Robert F. Goheen during his twelve years as President of Princeton University. The emphasis is on the people whose responsibility it is to promote and defend the principles underlying the modern American university-students, faculty, administrators, trustees, alumni. Several fundamental themes emerge the theme of individual responsibility, and the ever-present need to join rational intelligence with moral commitment, for example. Dr. Goheen sees the university as a continuing institution with long range goals, responding conservatively (in its best sense) to the human needs of the times. He seeks to define its institutional relationships in the context of the university's tasks in educ1tion and research, which must be understood and kept in balance if universities are to serve their functions effectively.Originally published in 1969.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.